A UV type coating, preparation method and application

By using UV-type coatings with specific ratios, the problems of erosion and low yield of UV coatings when coating PC+GF materials in the prior art are solved, and an efficient coating and environmentally friendly production process is achieved.

CN116875176BActive Publication Date: 2025-03-28SHANDONG JINGHONG INTELLIGENT TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210939772.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-05
Publication Date
2025-03-28
Estimated Expiration
2042-08-05

AI Technical Summary

Technical Problem

When existing UV coatings are coated on PC+GF materials, chemical coating corrosion can easily cause the fiberglass head to float, causing poor appearance, and low coating yield and environmental protection problems.

Method used

Using a UV-shaped coating including solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbon modified polyurethane acrylate, photoinitiator, leveling agent, polyethylene wax paste, modified silica and diluent, the corrosion of the chemical coating on the PC+GF substrate by specific ratios and preparation methods is reduced, and the rapid surface drying characteristics of the coating are improved.

Benefits of technology

The coating yield of PC+40% GF material products is improved, and the coating unit and energy consumption of the product is reduced. The yield can reach 80-85%, meeting the needs of batch production and does not require separate ultraviolet curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a UV type coating, a preparation method and an application. The UV type coating includes solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbon modified polyurethane acrylate, photoinitiator, leveling agent, polyethylene wax slurry, modified silicon dioxide and diluent, which can reduce the erosion of chemical coating on PC+GF substrate, cooperate with the fast surface drying characteristics of its own coating, improve the coating yield of PC+40%GF material products, and reduce the coating unit consumption and energy consumption of products. The preparation method of UV type coating is simple, highly repeatable, and can be used for large-scale industrial production. Electronic products prepared with UV type coating can greatly improve the coating yield of product shells, and are particularly suitable for shell products made of PC+GF materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a UV type coating, a preparation method and an application thereof. Background Art

[0002] UV coating refers to coating that is cured by UV radiation. UV curing coating can be applied to ink printing and exposed to UV radiation. Its solid content can be as high as 100%, so there is no volatile component and it does not pollute the environment. The high solid content also allows it to be applied to very thin films. UV curing coating can also be used to coat glass and plastic, wood, aluminum beverage bottles, etc.

[0003] At present, mobile phones and wearable devices are developing rapidly, and products are gradually converging towards several major terminal brands. At the same time, competing products are highly homogenized and competition is becoming increasingly fierce. Cost has always been one of the important factors in improving the core competitiveness of products. Taking mobile phones as an example, the shell materials of high-end products are basically high-cost materials such as metal, glass, and ceramics, while the shells of mid- and low-end products are basically low-cost plastic materials. Through paint decoration, the plastic material presents a gorgeous effect, achieving a more high-end appearance at a lower cost and increasing the added value of the product.

[0004] In the 3C market, in order to control costs, terminal brands basically use PC and PC plus glass fiber reinforced materials (PC+GF for short) as the main materials for product shells. Among them, PC+GF materials are more and more widely used. They are characterized by low cost, high strength, low shrinkage, good dimensional stability, easy molding, and high cost performance. They are particularly suitable as shell materials for handheld phones and wearable devices. Their disadvantage is that during painting, chemical coating erosion can easily cause the glass fiber heads to float out, resulting in poor appearance. Wearable products made of PC+40% GF are more prone to this problem due to their high glass fiber content.

[0005] In the prior art, a Chinese invention patent with application number CN201910037605.0 discloses a high-hiding UV treatment agent and its treatment process. Because TMPTA and HDDA acrylic monomers are added to its ingredients, it is very easy to corrode the material, and the yield on PC+40% GF material is extremely low. At the same time, toluene solvent is also used, which does not meet the increasingly stringent environmental protection requirements. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the disadvantages of the above-mentioned prior art and provide a UV type coating with high coating yield, a preparation method and an application.

[0007] The technical solution adopted to solve the above technical problems is: a UV type coating, which includes the following substances in the following mass proportions:

[0008]

[0009] Furthermore, the UV type coating also includes a leveling agent.

[0010] Furthermore, the leveling agent is polyether-modified polydimethylsiloxane.

[0011] Furthermore, the 184 photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0012] Furthermore, the TPO photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0013] Furthermore, the diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol, and the mass ratio is:

[0014]

[0015] A method for preparing a UV type coating comprises the following steps:

[0016] S1. Mix 184 photoinitiator and leveling agent with the first part of diluent, disperse at a speed of 500-600 rpm for 10-15 minutes, and prepare solution A;

[0017] S2, the solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbon modified polyurethane acrylate and the second part of diluent are mixed and dispersed uniformly, dispersed at a speed of 800±50 rpm for 25 to 30 min, and then modified silicon dioxide is added, dispersed at a speed of 1000±50 rpm, a temperature of 40 to 50° C., and a time of 25 to 30 min to prepare solution B;

[0018] S3, adding the solution A, polyethylene wax slurry and the third part of diluent into the solution B and mixing for 10 to 20 minutes, filtering through a 400-mesh filter cloth to obtain a UV type coating.

[0019] Furthermore, in the step S1, the mass ratio of the total mass of the 184 photoinitiator and the leveling agent to the mass ratio of the first part of the diluent is 1:3.

[0020] Furthermore, in step S1, the first part of the diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, in step S2, the second part of the diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, and in step S3, the third part of the diluent accounts for 1 / 2 to 1 / 3 of the total mass of the diluent.

[0021] An application of UV type coating, and the application of the UV type coating in the preparation of electronic products.

[0022] Furthermore, the electronic products include 3C products.

[0023] The beneficial effects of the present invention are as follows:

[0024] (1) The UV coating of the present invention comprises solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbonate modified polyurethane acrylate, photoinitiator, leveling agent, polyethylene wax slurry, modified silica and diluent, which can reduce the erosion of chemical coating on PC+GF substrate, cooperate with the fast surface drying characteristics of its own coating, improve the coating yield of PC+40% GF material products, and reduce the coating unit consumption and energy consumption of the products.

[0025] (2) The UV coating of the present invention is actually applied to electronic products, and the yield rate can reach 80-85%, which can fully meet the needs of mass production.

[0026] (3) The UV type coating of the present invention needs to be used in combination with a vacuum coating primer and does not require separate UV curing. It can be sprayed with the primer. The polycarbonate type polyurethane acrylate component is the main component in the vacuum coating primer, so it can well receive the primer and has good interlayer adhesion.

[0027] (4) The preparation method of the UV type coating of the present invention is simple, highly repeatable, and can be used for large-scale industrial production.

[0028] (5) Electronic products made with UV-type coatings can greatly improve the coating yield of product shells, and are particularly suitable for shell products made of PC+GF materials. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Example 1

[0031] The mass ratio of substances in the UV type coating is: 8 parts of solvent-based modified polyurethane acrylate, 14 parts of thermoplastic acrylic resin, 15 parts of polycarbonate modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent.

[0032] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the weight ratio of the materials used is: 93.6g of solvent-based modified polyurethane acrylate, 163.7g of thermoplastic acrylic resin, 175.4g of polycarbonate modified polyurethane acrylate, 23.4g of 184 photoinitiator, 4.7g of TPO photoinitiator, 1.2g of leveling agent, 58.5g of polyethylene wax slurry, 11.7g of modified silica, and 467.5g of diluent.

[0033] The solvent-based modified polyurethane acrylate is selected from one or more of Changxing Chemical 6175-3, Wuxing New Material W3075, Qinggang New Material WD5145, Changsha Unico New Material UV409. The functionality of the solvent-based modified polyurethane acrylate is 3-4. The solvent-based modified polyurethane acrylate is an acrylic acid-modified polyurethane resin. The resin has good adhesion to PC materials, and the theoretical functionality is 3-4.

[0034] The thermoplastic acrylic resin is selected from one or more of Lihuaxin LF-1117, Bolier BM70, and DSM B-805. The glass transition temperature of the thermoplastic acrylic resin is 90-110°. The thermoplastic acrylic resin is a resin with a high glass transition temperature. The characteristic of the thermoplastic acrylic resin is that it can be well dissolved in UV resin. Thermoplastic resin has a large molecular weight and poorer fluidity than UV resin. It has good solvent release and can dry quickly. Therefore, it can promote solvent release in the primer, reduce the fluidity of the paint film, dry quickly, and form covering power on the substrate, especially covering floating fibers.

[0035] The polycarbon modified polyurethane acrylate is selected from one or more of Changxing Chemical 6157B-80, Shanghai Difeng DF6372, Zhanxin 1114, Dongguan Fengjin FJ228, and Jiuwei Trade UA-522PC. The polycarbon modified polyurethane acrylate is difunctional, and the characteristics of this type of resin are fast curing speed, high temperature resistance and good water resistance. Polycarbonate is commonly known as PC, especially has good adhesion to PC materials. Therefore, the present invention has good adhesion to PC and PC+GF materials, and excellent water boiling resistance. In practical applications, the product coated with the present invention has good adhesion after being boiled in 100°C boiling water for 120 minutes, and does not bubble.

[0036] The 184 photoinitiator is 1-hydroxycyclohexyl phenyl ketone, and the TPO photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0037] The leveling agent used is BYK306 from BYK of Germany, the 184 photoinitiator used is JRCure-1104 from Jiuri, the TPO photoinitiator used is JRCure-1108 from Jiuri, and the leveling agent is BYK306 purchased from BYK of Germany. The leveling agent is used to reduce the surface tension of UV coatings, thereby improving their wettability to the substrate surface and preventing shrinkage cavities and oil pits.

[0038] The polyethylene wax slurry is selected from Gifu wax slurry T-10P-5, and the modified silica is selected from one or more of Japan Tosoh E-1011, Grace C803, and Degussa TS-100. The polyethylene wax slurry and modified silica can adjust the mattness of the paint film, improve the rheology of the paint film, and make it have stronger hiding power, thereby promoting the improvement of the yield rate.

[0039] The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol. The mass proportion of the material in 40 parts of the diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol. The corresponding weight proportion of the material used in 467.5g of the diluent is: 280.5g of ethyl acetate, 93.5g of acetone, 46.75g of propylene glycol methyl ether, and 46.75g of diacetone alcohol. The diluent used is a diluent with fast volatility and strong solubility, which is compounded with a small amount of solvent that evaporates slowly and has weak solubility. The fast-drying strong solvent can reduce the viscosity of the coating and is easy to construct. During the spraying construction process, the fast-drying strong solvent evaporates directly after leaving the spray gun nozzle, and a very small part reaches the surface of the workpiece and evaporates quickly, so it will not form a swelling effect on the surface of the material, and the glass fiber head will not emerge. Slow-drying weak solvents Due to their characteristics, weak solvents cannot swell PC materials and will not cause floating fiber defects. Diluents can improve the coating yield.

[0040] The UV coating also includes a leveling agent, which is purchased from BYK, Germany, and is a leveling agent of model BYK306, and the leveling agent is polyether-modified polydimethylsiloxane. The leveling agent can reduce the surface tension of the UV coating, thereby improving its wettability to the substrate surface and preventing shrinkage cavities and oil pits.

[0041] The preparation method of UV type coating comprises the following steps:

[0042] S1. Mix 184 photoinitiator and leveling agent with the first part of diluent, wherein the first part of diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, and the mass ratio of the total mass of 184 photoinitiator and leveling agent to the first part of diluent is 1:3. Disperse at a speed of 500 to 600 rpm for 10 to 15 minutes to prepare solution A;

[0043] S2, the solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbon modified polyurethane acrylate and the second part of diluent are mixed and dispersed uniformly, the second part of diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, and the mixture is dispersed and mixed uniformly at a speed of 800±50 rpm for 25 to 30 min, and then modified silicon dioxide is added, and the mixture is dispersed at a speed of 1000±50 rpm, a temperature of 40 to 50°C, and a time of 25 to 30 min to prepare solution B;

[0044] S3. Add the solution A, polyethylene wax slurry and the third part of diluent into solution B and stir and mix for 10 to 20 minutes, wherein the third part of diluent accounts for 1 / 2 to 1 / 3 of the total mass of the diluent. Filter through a 400-mesh filter cloth to obtain a UV coating.

[0045] Example 2

[0046] The mass proportion of the materials in the UV type coating is: 9.5 parts of solvent-based modified polyurethane acrylate, 12 parts of thermoplastic acrylic resin, 17 parts of polycarbon modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent. The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol. The mass proportion of the materials in 40 parts of the diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol.

[0047] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the weight ratio of the materials used is: 109.2g of solvent-based modified polyurethane acrylate, 137.9g ​​of thermoplastic acrylic resin, 195.4g of polycarbonate modified polyurethane acrylate, 23g of 184 photoinitiator, 4.6g of TPO photoinitiator, 1.1g of leveling agent, 57.5g of polyethylene wax slurry, 11.5g of modified silica, and 459.8g of diluent. The weight ratio of the materials in 459.8g of diluent is 275.8g of ethyl acetate, 92g of acetone, 46g of propylene glycol methyl ether, and 46g of diacetone alcohol.

[0048] The preparation method and application are the same as those of Example 1.

[0049] Example 3

[0050] The mass proportion of the materials in the UV type coating is: 11 parts of solvent-based modified polyurethane acrylate, 10.5 parts of thermoplastic acrylic resin, 19 parts of polycarbon modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent. The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol, and the mass proportion of the materials in 40 parts of the diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol.

[0051] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the mass ratio of the materials used is: 123.6g of solvent-based modified polyurethane acrylate, 118g of thermoplastic acrylic resin, 213.5g of polycarbonate modified polyurethane acrylate, 22.5g of 184 photoinitiator, 4.5g of TPO photoinitiator, 1.1g of leveling agent, 56.2g of polyethylene wax slurry, 11.2g of modified silica, and 449.4g of diluent. In the 449.4g of diluent, there are 269.7g of ethyl acetate, 89.9g of acetone, 44.9g of propylene glycol methyl ether, and 44.9g of diacetone alcohol.

[0052] The preparation method and application are the same as those of Example 1.

[0053] Example 4

[0054] The mass proportion of the materials in the UV type coating is: 12.5 parts of solvent-based modified polyurethane acrylate, 8.5 parts of thermoplastic acrylic resin, 21 parts of polycarbon modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent. The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol. The mass proportion of the materials in 40 parts of the diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol.

[0055] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the mass ratio of the materials used is: 138.1g of solvent-based modified polyurethane acrylate, 93.9g of thermoplastic acrylic resin, 232.1g of polycarbonate modified polyurethane acrylate, 22.1g of 184 photoinitiator, 4.4g of TPO photoinitiator, 1.1g of leveling agent, 55.2g of polyethylene wax slurry, 11.1g of modified silica, and 442g of diluent. In the 442g of diluent, there are 265.2g of ethyl acetate, 88.4g of acetone, 44.2g of propylene glycol methyl ether, and 44.2g of diacetone alcohol.

[0056] The preparation method and application are the same as those of Example 1.

[0057] Example 5

[0058] The mass ratio of substances in the UV type coating is: 14 parts of solvent-based modified polyurethane acrylate, 6.5 parts of thermoplastic acrylic resin, 22 parts of polycarbon modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent, wherein the diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol, and the mass ratio of substances in 40 parts of diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol.

[0059] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the mass ratio of the materials used is: 153.8g of solvent-based modified polyurethane acrylate, 71.4g of thermoplastic acrylic resin, 241.8g of polycarbonate modified polyurethane acrylate, 22g of 184 photoinitiator, 4.4g of TPO photoinitiator, 1.1g of leveling agent, 54.9g of polyethylene wax slurry, 11g of modified silica, and 439.6g of diluent. In the 439.6g of diluent, there are 263.76g of ethyl acetate, 87.92g of acetone, 43.96g of propylene glycol methyl ether, and 43.96g of diacetone alcohol.

[0060] The preparation method and application are the same as those of Example 1.

[0061] Example 6

[0062] The mass proportion of the materials in the UV type coating is: 15 parts of solvent-based modified polyurethane acrylate, 5 parts of thermoplastic acrylic resin, 24 parts of polycarbon modified polyurethane acrylate, 2 parts of 184 photoinitiator, 0.4 parts of TPO photoinitiator, 0.1 parts of leveling agent, 5 parts of polyethylene wax slurry, 1 part of modified silica, and 40 parts of diluent. The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol, and the mass proportion of the materials in 40 parts of the diluent is: 30 parts of ethyl acetate, 10 parts of acetone, 5 parts of propylene glycol methyl ether, and 5 parts of diacetone alcohol.

[0063] Correspondingly, taking the production of 1000g of the UV type coating of the present invention as an example, the mass ratio of the materials used is: 162.2g of solvent-based modified polyurethane acrylate, 54.1g of thermoplastic acrylic resin, 259.5g of polycarbonate modified polyurethane acrylate, 21.6g of 184 photoinitiator, 4.3g of TPO photoinitiator, 1g of leveling agent, 54.1g of polyethylene wax slurry, 10.8g of modified silica, and 432.4g of diluent, 259.44g of ethyl acetate, 86.48g of acetone, 43.24g of propylene glycol methyl ether, and 43.24g of diacetone alcohol in the diluent.

[0064] The preparation method and application are the same as those of Example 1.

[0065] Comparative Example 1

[0066] The difference between a UV type coating of this comparative example and Example 6 is that this comparative example uses 3 parts by weight of TMPTA monomer, which is selected from the trade name Changxing Chemical EM231, to replace 5 parts by weight of the solvent-based modified polyurethane acrylate in Example 6.

[0067] The weight portions of other substances in this comparative example 1 are equal to those in Example 6.

[0068] Comparative Example 2

[0069] The difference between a UV type coating of this comparative example and Example 6 is that this comparative example uses 3 parts by weight of HDDA monomer, which is selected from the trade name Changxing Chemical EM221, to replace 5 parts by weight of solvent-based modified polyurethane acrylate in Example 6.

[0070] The weight portions of other substances in this comparative example 1 are equal to those in Example 6.

[0071] Comparative Example 3

[0072] The difference between a UV type coating of this comparative example and Example 6 is that 5 parts by weight of diacetone alcohol organic solvent in Example 6 is replaced by 5 parts by weight of cyclohexanone in this comparative example.

[0073] The weight portions of other substances in this comparative example 1 are equal to those in Example 6.

[0074] Application Examples

[0075] The application of UV coatings in the preparation of electronic products, including 3C products, can greatly improve the coating yield of product shells, and is particularly suitable for shells made of PC+GF materials.

[0076] In this application example, the UV coating obtained in Examples 1 to 6 and Comparative Examples 1 to 3 is applied to the surface of the smart watch case by flat spraying, specifically comprising the following steps:

[0077] D1. The UV coatings obtained in Examples 1 to 6 and Comparative Examples 1 to 3 are sprayed on the smart watch case substrate made of PC + 40% GF, with a coating film thickness of 15 to 25 μm, and leveled at 50 to 60° C. for 5 to 8 minutes, and then the primer is sprayed;

[0078] D2, spray vacuum coating primer on the surface of the primer film obtained in step D1, the model of vacuum coating primer is Matsui PEB10477A, ​​the coating film thickness is 22-28 μm, and after leveling at 50-60°C for 5-8 minutes, the vacuum coating primer is sprayed at 700-900 mJ / cm 2 Solidification under the energy of

[0079] D3. Perform vacuum coating on the cured surface. The coating material is indium and the coating thickness is about 20 to 40 nanometers.

[0080] D4. Spray vacuum coating intermediate paint on the coating layer. The model of vacuum coating intermediate paint is Matsui PEM20308A. The coating film thickness is 6-8μm. After leveling for 5-8min at 60-65℃, spray at 400-600mJ / cm 2 Solidification under the energy of

[0081] D5. Spray vacuum coating topcoat on the surface of vacuum coating midcoat. The model of vacuum coating topcoat is PET00485A. The coating film thickness is 20-25μm. After leveling at 60-70℃ for 6 minutes, the coating film thickness is 2000-1200mJ / cm 2 The smart watch case is obtained by curing under the energy of.

[0082] Test example

[0083] This test example tests the basic performance and yield of the paint film on the smart watch case obtained in the application example. The specific results are shown in Table 1. Among them, the adhesion test is carried out with reference to the standard document numbered GB9286~1998, and the adhesion grade is calculated according to ASTM.

[0084] The yield rate refers to the appearance inspection after the vacuum coating primer is cured. The main types of defective items are as follows: glass fiber spots, environmental particles, oil stains and material defects. The yield rate of this experiment is the data after excluding the above defective ratios.

[0085] Table 1 Performance results of mobile phone cases obtained in application examples

[0086]

[0087]

[0088] Table 1 Results: The adhesion performance and yield of the paint films obtained in Examples 1 to 6 meet the requirements of mass production; the reason why the water boiling adhesion and appearance of Examples 1 to 2 are relatively poor is that the content of thermoplastic acrylic resin is high and it is not resistant to water boiling.

[0089] Compared with Example 6, Comparative Example 1 replaces part of the solvent-based modified polyurethane acrylate with TMPTA monomer, and its components have a negative impact on water boiling and yield.

[0090] Compared with Example 6, Comparative Example 2 replaces part of the solvent-based modified polyurethane acrylate with HDDA monomer, and its components have a negative impact on water boiling and yield.

[0091] Compared with Example 6, in Comparative Example 2, part of the diacetone alcohol weak solvent was replaced with a strong solvent cyclohexanone, whose components had a negative impact on water boiling and yield.

[0092] Some monomers are added in Comparative Examples 1 and 2, which are obviously not suitable for the current PC+GF materials. Since such materials have a microporous surface structure, monomers with strong permeability will penetrate into the pores and destroy the PC surface structure, causing the glass fiber to lose its suppression, resulting in poor floating fiber. At the same time, because the primer is UV-cured together with the vacuum plating primer, the coating in the pores is not completely cured due to insufficient light intensity, and oozes out and bubbles during the water boiling test, and the adhesion becomes poor. Similarly, slow-drying strong solvents are added in Comparative Example 3, which will also corrode the material, causing floating fibers, and the same problem occurs when boiling in water.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.

Claims

1. A UV type coating, characterized in that: The UV type coating comprises the following substances in the following mass proportions: The 184 photoinitiator is 1-hydroxycyclohexyl phenyl ketone; The TPO photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; The diluent is at least one or more of ethyl acetate, propylene glycol methyl ether, acetone and diacetone alcohol, and the mass ratio is: The UV type coating also includes a leveling agent, and the leveling agent is polyether-modified polydimethylsiloxane.

2. A method for preparing the UV type coating according to claim 1, characterized in that: The following steps are involved: S1. Mix 184 photoinitiator and leveling agent with the first part of diluent, disperse at a speed of 500-600 rpm for 10-15 minutes, and prepare solution A; S2, the solvent-based modified polyurethane acrylate, thermoplastic acrylic resin, polycarbon modified polyurethane acrylate and the second part of the diluent are mixed and dispersed uniformly, dispersed at a speed of 800±50 rpm for 25-30 min, and then modified silicon dioxide is added, and dispersed at a speed of 1000±50 rpm, a temperature of 40-50° C., and a time of 25-30 min to prepare solution B; S3, adding the solution A, polyethylene wax slurry and the third part of diluent into the solution B and mixing for 10 to 20 minutes, filtering through a 400-mesh filter cloth to obtain a UV type coating.

3. The method for preparing the UV type coating according to claim 2, characterized in that: In the step S1, the mass ratio of the total mass of the 184 photoinitiator and the leveling agent to the mass ratio of the first part of the diluent is 1:

3.

4. The method for preparing the UV type coating according to claim 2, characterized in that: In step S1, the first part of the diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, in step S2, the second part of the diluent accounts for 1 / 4 to 1 / 3 of the total mass of the diluent, and in step S3, the third part of the diluent accounts for 1 / 2 to 1 / 3 of the total mass of the diluent.

5. An application of the UV type coating according to claim 1, characterized in that: The application of the UV type coating in the preparation of electronic products.

6. The use of the UV type coating according to claim 5, characterized in that: The electronic products include 3C products.

Citation Information

Patent Citations

  • High-shielding UV treatment agent and treatment process thereof

    CN109810627A

  • Ultraviolet curing processing agent

    CN102199377A

  • High-performance vacuum electroplating UV (Ultraviolet) coating and preparation method thereof

    CN108676488A

  • Vacuum plating laser etching protective paint as well as preparation method and application thereof

    CN116731603A